A new TICT and AIE-active tetraphenylethene-based Schiff base with reversible piezofluorochromism. Issue 72 (18th July 2016) - Han, Fangfang; Zhang, Ran; Zhang, Zhaoming; Su, Jianguo; Ni, Zhonghai
Abstract : A new tetraphenylethene-based Schiff base N -5-nitrosalicylidene-4-tetraphenylethenylamine (NSTPE ) exhibits an interesting "on–off–on" optical switching property and reversible piezofluorochromic properties. Abstract : A new tetraphenylethene-based Schiff base N -5-nitrosalicylidene-4-tetraphenylethenylamine (NSTPE ) was synthesized based on 4-tetraphenylethenylamine and 5-nitrosalicylaldehyde, and its structure was fully characterized by 1 H NMR, 13 C NMR, MS and single crystal X-ray diffraction analysis. The study of optical properties shows that the emission exhibits an interesting "on–off–on" switching property with a U-shaped tendency when adding water into the tetrahydrofuran solution ofNSTPE, showing twisted intramolecular charge transfer (TICT) and aggregation-induced emission (AIE) characteristics. Moreover, the compound exhibits reversible piezofluorochromic properties.